1999
DOI: 10.1046/j.1471-4159.1999.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

The Astroglial ASCT2 Amino Acid Transporter as a Mediator of Glutamine Efflux

Abstract: Glutamine release from astrocytes is an essential part of the glutamate-glutamine cycle in the brain. Uptake of glutamine into cultured rat astrocytes occurs by at least four different routes. In agreement with earlier studies, a significant contribution of amino acid transport systems ASC, A, L, and N was detected. It has not been determined whether these systems are also involved in glutamine efflux or whether specific efflux transporters exist. We show here that ASCT2, a variant of transport system ASC, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In this work, different assays have been employed to shed light on the substrate specificity of hASCT2; this represents a vintage but very relevant issue in the understanding of hASCT2 biology in both physiological and pathological conditions with potential outcomes in pharmacology. In line with very early but disregarded observations on mice and rat ASCT2 (Utsunomiya-Tate et al, 1996;Broer et al, 1999;Oppedisano et al, 2007), the capacity of the hASCT2 to mediate a Na + and H + dependent glutamate ex /glutamine in antiport emerged. The rate of this reaction is comparable to the well-assessed antiport of neutral amino acids (Figure 3B).…”
Section: Transport Of Glutamate Via Hasct2mentioning
confidence: 85%
See 1 more Smart Citation
“…In this work, different assays have been employed to shed light on the substrate specificity of hASCT2; this represents a vintage but very relevant issue in the understanding of hASCT2 biology in both physiological and pathological conditions with potential outcomes in pharmacology. In line with very early but disregarded observations on mice and rat ASCT2 (Utsunomiya-Tate et al, 1996;Broer et al, 1999;Oppedisano et al, 2007), the capacity of the hASCT2 to mediate a Na + and H + dependent glutamate ex /glutamine in antiport emerged. The rate of this reaction is comparable to the well-assessed antiport of neutral amino acids (Figure 3B).…”
Section: Transport Of Glutamate Via Hasct2mentioning
confidence: 85%
“…In the frame of substrate specificity, previous results showed that some transporters of the SLC1 family, as well as their bacterial homologs, can be forced to switch the specificity from neutral amino acids to acidic ones (glutamate or aspartate) or vice versa, by mutating some specific residues (Scopelliti et al, 2013(Scopelliti et al, , 2018Canul-Tec et al, 2017). Noteworthy, besides these artificial mutations, the very first report on mice ASCT2 showed Na + and pH-dependent transport of glutamate with a Km in the millimolar range, indicating a lower affinity compared to that of neutral amino acids (Utsunomiya-Tate et al, 1996;Broer et al, 1999). Then, it was shown that glutamate triggered the glutamine efflux in rat astrocytes but without a definitive molecular explanation (Deitmer and Rose, 1996;Broer and Brookes, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…From the findings obtained in different experimental systems, it can be deduced that the main physiological role of ASCT2 consists in mediating cell uptake of glutamine and balancing the amino acid pools in several tissues. ASCT2 has been also reported to be involved in the glutamine/glutamate cycle between astrocytes and neurons allowing for both the recycle of glutamate from the synaptic cleft in astrocytes and its re-synthesis in neurons (Broer et al, 1999; Leke and Schousboe, 2016). However, it has to be stressed that the enormous interest in ASCT2 derives from the well-acknowledged involvement in cancer development and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been speculated if L-cystine derivatives, like L-2-oxothiazolidine-4-carboxylic acid (OTC), could have interactions with EAATs and, thus, be used as selective promoieties to carry parent drugs in a prodrug form, like in the case of D-264, a neuroprotective agent that has been studied in the treatment of PD (Figure 2) [29]. Although ASCT1 (SLC1A4) and ASCT2 (SLC1A5) are ubiquitously expressed throughout the body, they are also found in the brain; mainly in neurons and astrocytes, but also to some extent at the BBB (Table 1) [5,[30][31][32][33][34]. Both ASCT1s mediate sodium-and pH-dependent transport of several neutral amino acid substrates, not only L-alanine, Lserine, and L-cystine (ASCT1 only), but also L-glycine, L-methionine, L-valine, L-leucine, L-isoleucine, and L-threonine.…”
Section: Glutamate and Neutral Amino Acid Transporter Family (Slc1a)mentioning
confidence: 99%